Testing conditionality with Bourdieu's capital theory: How economic, social, and embodied cultural capital are associated with diet and physical activity in the Netherlands - Andrea L. Mudd; Joost Oude Groeniger; Michèlle Bal; Sanne E. Verra; Frank J. van Lenthe; Carlijn B.M. Kamphuis (Elsevier, 2023)
Although Bourdieu's capital theory emphasized that economic, social, and embodied cultural capital interact to shape health behavior, existing empirical research mainly considered separate associations of the three forms of capital. Our aim was to investigate if and how economic, social, and embodied cultural capital are conditional on each other in their associations with adults' diet and physical activity.Cross-sectional, self-reported data from the 2014 GLOBE survey of 2812 adults aged between 25 and 75 years residing in Eindhoven, the Netherlands were used. Step-wise multiple logistic regression models included economic, social, and embodied cultural capital and adjustment for potential confounders. The models estimated odds ratios of main effects and two-way interactions of the forms of capital with fruit consumption, vegetable consumption, sports participation, and leisure time walking or cycling.In the main effects models, embodied cultural capital was consistently positively associated with all outcomes. Social capital was positively associated with sports participation, fruit consumption, and vegetable consumption, and economic capital was positively associated with sports participation and vegetable consumption. In the two-way interaction models, having specific higher levels of both economic and social capital strengthened their positive association with sports participation. No other combinations of capital were conditional on each other.Economic and social capital were conditional on each other in their association with sports participation, so interventions that provide both economic and social support may be especially effective for increasing this type of physical activity. As its association was strong with all outcomes but not conditional on other forms of capital, embodied cultural capital may operate distinctly from economic and social resources. Policy that takes differences in embodied cultural capital into account or changes to the environment that dampen the importance of embodied cultural resources for health behavior may help improve both diet and physical activity.